A review of analytical methods for the determination of four new phosphodiesterase type 5 inhibitors in biological samples and pharmaceutical preparations - Cristiane Franco Codevilla; Tamara dos Santos Castilhos; Ana Maria Bergold (Universidade de São Paulo, 2013)
The introduction of oral phosphodiesterase type 5 inhibitor therapy in 1998 revolutionized the treatment of erectile dysfunction. Erectile dysfunction is the most common sexual problem in men. It often has a profound effect on intimate relationships and quality of life. The analysis of pharmaceuticals is an important part of the drug development process as well as for routine analysis and quality control of commercial formulations. Whereas the determination of sildenafil citrate, vardenafil and tadalafil are well documented by a variety of methods, there are few publications about the determination of udenafil, lodenafil carbonate, mirodenafil and avanafil. The paper presents a brief review of the action mechanism, adverse effects, pharmacokinetics and the most recent analytical methods that can determine drug concentration in biological matrices and pharmaceutical formulations of these four drugs. A introdução da terapia oral com inibidores da fosfodiesterase tipo 5, em 1998, revolucionou o tratamento da disfunção erétil. A disfunção erétil é o problema sexual mais comum em homens. Muitas vezes tem um efeito profundo nas relações íntimas e na qualidade de vida. A análise de produtos farmacêuticos é uma parte importante do processo de desenvolvimento de fármacos, bem como para a análise de rotina e controle de qualidade das formulações comerciais. Enquanto a determinação do citrato de sildenafila, vardenafila e tadalafila está bem documentada por uma variedade de métodos, existem poucas publicações sobre a determinação de udenafila, carbonato de lodenafila, mirodenafila e avanafila. O artigo apresenta uma breve revisão do mecanismo de ação, efeitos adversos, farmacocinética e os mais recentes métodos analíticos, que podem determinar a concentração do fármaco em matrizes biológicas e formulações farmacêuticas destes quatro fármacos.